POSTNATAL ENCEPHALITIS: A DIAGNOSIS NOT TO BE MISSED - Naz, Farhat; Malik, Saqib; Mehmood, Tariq; Tariq, Sumbal (Journal of Ayub Medical College Abbottabad, 2012)
Background: Viral encephalitis is a common condition but only a few studies are available on occurrence of viral encephalitis in postnatal women. The objective of this study was to determine the frequency of postnatal encephalitis among patients presenting with cerebral neurological complications during puerperium and to determine a response to 10 day course of acyclovir therapy and final outcome of the patients. Methods: This cross-sectional descriptive study was conducted at Department of Medicine, Unit A, Ayub Teaching Hospital, Abbottabad from Jan to Dec 2011. All patients presenting with encephalitis in their postnatal period were enrolled. Eclampsia patients were excluded from study. The diagnosis of encephalitis was made on clinical assessment, CSF routine examination, CT scan and MRI. Results: Among patients 16 (84.2%) presented with fever, 13 (68.42%) with headache, 8 (42.1%) with meningeal irritation, 7 (36.84%) with hemiparesis, 18 (94.7%) with altered sensorium, 13 (68.42%) with seizures, and 7 (36.84%) with coma. Cerebrospinal fluid of 16 (84.21%) patient had the changes consistent with viral encephalitis. It was normal in 2 (10.52%) patients and showed picture of pyogenic meningitis in 1 (5.26%) cases. On CT scan of brain, 3 (15.78%) had normal scans, 3 (15.78%) had cerebral oedema, 4 (21.05%) had ischemic infarct, 3 (15.78%) had meningo-encephalitis, 2 (10.52%) had infarct plus cerebral oedema, 1 (5.26%) had encephalitis and 3 (15.78%) had infarct plus haemorrhage. On MRI brain 15 out of 17 (88.2%) had lesions consistent with encephalitis. All 19 (100%) patients were treated with 10 days course of acyclovir and a broad spectrum third generation antibiotic. After hospitalisation 11 (57.8%) patients were discharged with complete recovery, 5 (26.31%) were discharged with partial recovery and 3 (15.78%) patients expired. Conclusion: Clinical presentation of the patient is most important in diagnosing viral encephalitis in postnatal women especially when patient presents with fever, altered sensorium and convulsions. Acyclovir therapy should be started without delay while awaiting other investigations. Keywords: Encephalitis, postnatal, acyclovir